Audit Firm Type and Sustainability Performance: A Study of Quoted Oil and Gas Marketing Companies in Nigeria - Aminu Abdullahi; Oladele Jami’u Olanrewaju; Moshud Nurudeen Mohammed (Training & Research Institute - Jeramba Ilmu Sukses, 2021)
The study specifically examines the impact of audit firm types on sustainability performance effort (health care, employment and education) of quoted oil and gas marketing company in Nigeria. The population of the study consists of all the 13 oil and gas marketing companies quoted on the Nigeria Stock Exchange as at end of the year 2020. Secondary data was sourced from the annual reports and accounts of the sampled companies for the period of 5 years (2016-2020). The dependent variables for the study were Sustainability Performance effort proxied by expenditure on education, employment and health care by the oil and gas companies, while the independent variable was audit firm type. A panel regression model was employed for the analysis as the data cuts across different firms over periods. The results revealed that there is no significant relationship between audit firm type and sustainability performance. This is evident from the p-value of 0.554 which is related to audit firm type and health care. Also, the result of the audit firm and education revealed a p-value of 0.422 and that of audit firm type and employment 0.364. This result provided a basis for rejecting all the hypotheses. The study therefore, recommends that the oil and gas companies should continue to undertake their responsibility in the sustainability performance without any reference to whether they are being audited by any type of audit firm